To what extent do school leaders in Slovenia understand physical school environments as a learning factor? - Cencic, Majda (CEPS journal, 2017)
School leaders are a central factor of the quality of learning and teaching in schools. It is generally believed that the staff model their behavior on leaders, which means if school leaders understand the physical school environment to be an important factor of learning, school staff (teachers and other professional staff) will also do so. To discover how school leaders assess the school environment as a factor of learning, 150 school leaders in primary education in Slovenia were invited to complete an online questionnaire. They were asked about their views regarding to what extent their school as physical environment encouraged certain factors. Fourteen listed factors were assessed on five-point numeric scales. The results show that in their school environment, school leaders assessed ecology, movement, and respect the highest, and feelings, imagination, and space the lowest. Their estimates of the assessed factors differ depending on the type of school building (new, old, renovated) only on the factors of movement, creativity, and logic and mathematics in favour of old schools. The results provide interesting information especially for school policy and everyone involved in the planning, building, or renewal of school premises. (DIPF/Orig.).